PERCEPTION LEVEL OF TIKTOK APPLICATION AMONG IPGKTI STEM TRAINEE TEACHERS IN TEACHING AND LEARNING - Khairuddin, Nor’aida; Bahaudin, Mohd Zulfahmi; Ahmad, Khalidah; Abdul Wahab, Nur Bahiyah; Kasmani, Halina (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2025)
Innovative teaching methods in STEM education are essential for fostering engagement, creativity, and problem-solving. Despite the popularity of TikTok as a short-form video platform, little research has examined its educational potential within teacher training, particularly in STEM contexts. This study investigates the perception level of the TikTok application among STEM trainee teachers at Temenggong Ibrahim Teacher Training Campus (IPGKTI), focusing on its implications for teaching and learning. Guided by the Technology Acceptance Model (TAM), the survey instrument comprised 13 items across five sub-constructs ease of use, educational value, engagement potential, content quality and relevance, and social influence adapted from the Standards for Educational and Psychological Testing (AERA, APA, & NCME, 2014). Data were collected through purposive sampling of 88 STEM trainee teachers. The instrument demonstrated strong internal consistency (Cronbach’s alpha = 0.89; sub-constructs = 0.78–0.86). Rasch Measurement Model confirmed scale robustness (person reliability = 0.84; item reliability = 0.90). Inferential analysis using independent samples t-tests and ANOVA revealed no significant differences in perception across gender, field of study, or years of study (p > .05; η² < 0.01). Item I5 (TikTok promotes creativity in STEM teaching) recorded the lowest agreement (mean logit = –0.42), while Item I2 (using TikTok to expand social networks) had the highest (mean logit = +0.61). These findings indicate that TikTok is widely perceived as a social networking tool but remains underutilised as a medium for creative STEM instruction. The results highlight a gap in digital pedagogical competence, suggesting the need for teacher training programs to embed TikTok-based microlearning and instructional design strategies. Such targeted training could transform TikTok from a networking platform into a pedagogically meaningful tool for innovative STEM education.